A patient with an hourglass shaped fractured coronary stent - Y. Andreou, Andreas; Tyrlis, Angelos (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
A 53-year-old female patient with a history of stent angioplasties in 2014 and coronary artery bypass graft surgery (CABG) to the left anterior descending and obtuse marginal arteries in 2016 underwent coronary angiography in July 2019 due to unstable angina. Both grafts were patent whereas the proximal right coronary artery (RCA) contained an intermediate in-stent stenosis which corresponded to an area of stent deformation with an inward displacement of the struts on both sides of the stent without discontinuity in the stent body (Figures 1 A, B). The stenosis was associated with an instantaneous wave-free ratio of 1.0. Intravascular ultrasound (IVUS) examination (Figures 1, 2) revealed a grossly distorted stent without strut malapposition or neointimal buildup (Figures 1 C and 2 panels 2, 6), which harboured an area with ulcerated atheroma and sparse stent struts indicating stent fracture (SF) (Figures 1 D and 2 panels 3–5). Proximal RCA angulation and hinge motion were observed in February 2014 before the successful implantation of a 3.5 mm × 28 mm biolimus A9-eluting BioMatrix Flex (Biosensor, Morges, Switzerland) stent in order to treat a catheter-induced dissection (Figure 3). Coronary angiography performed before CABG in March 2016 showed a structurally intact proximal RCA stent (Figure 4). Consequently, chronic stent recoil (SR) secondary to loss of radial strength of the stent due to late (> 1 year) SF attributed to mechanical fatigue was diagnosed. Angioplasty with a 3.75 mm non-compliant balloon and then a 3.75 mm paclitaxel-coated balloon was undertaken successfully (Figure 5). The patient was discharged on dual antiplatelet therapy to be taken for at least 12 months. Follow-up angiography at 6 months showed a patent stent without recurrent SR (Figure 6).